Repair and replication of plasmids with site-specific 8-oxodG and 8-AAFdG residues in normal and repair-deficient human cells. - Klein, J C (1992)
The in vivo mutagenicity of 7-hydro-8-oxo-2'-deoxyguanosine (8-oxodG) and N-(guanin-8-yl)-N-acetyl-2-aminofluorene (8-AAFdG) in human cells was determined by transfecting various cell lines with plasmids that carried a single adduct at a defined site. 8-OxodG is one of the many DNA modifications formed by oxygen radicals, and was found to be highly miscoding during replication with purified DNA polymerases in vitro. Here we show that the frequency of mutations induced by 8-oxodG during replication in vivo is at most only 2% above background. The most predominant mutation found was a single G----T transversion. The frequency of this transversion was found to be 3 to 5-fold increased in excision repair deficient XP-A cells. Interestingly, also the replication of 8-oxodG containing plasmids was significantly impaired (approximately 4-fold) in the XP-A cells, but not in HeLa cells, normal fibroblasts or XP-A revertant cells. When 8-AAFdG containing plasmids were used, the mutation frequencies did not exceed background levels (less than 2%) with any of the cell lines tested. The presence of 8-AAFdG almost completely inhibited plasmid replication (more than 50-fold) in XP-A cells. Apparently, both 8-AAFdG and 8-oxodG are not or poorly repaired in these cells, causing a block of DNA replication. This suggests that both lesions are substrates for excision repair, although to a varying extent.